Mundane reason and epistemic culture as organizational theory - Whiteley, Jervis (Curtin University of Technology, 2003)
Of great interest to organizational theorists are problems that arise within the sense-making domain. The paper introduces two important theories, both of which were results of empirical work. These are the theory of mundane reason and that of epistemic cultures. These theories together have a powerful impact on organizational theory. Building upon what we know, a Theory of Mundane Reason and Epistemic Culture is proposed. It is suggested that this constructivist approach to research may be justified as a meta-ontology. Mundane reason has been chosen because it has both a factuality and universality. Consequences of this include assumptions that directly impact on the ability to penetrate others? reality. This in turn impacts upon the ability to communicate effectively. Traditional models of communication used in the literature of management and marketing were a product of their time. Theories like the one presented here allow a re-thinking and re-theorising of communication models such as the one chosen as the example in the paper. The paper concludes with a formula for analysing faulty communication resulting from an unawareness of mundane reason and epistemic cultures.